x2y4-2xy2 + 1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(A+B=-12x^2y^4-6x^2y^4=-18x^2y^4\)
\(A+C=-12x^2y^4+9x^2y^4=-3x^2y^4\)
\(B+C=-6x^2y^4+9x^2y^4=3x^2y^4\)
a) A+B=−12x2y4−6x2y4=−18x2y4A+B=−12x2y4−6x2y4=−18x2y4
A+C=−12x2y4+9x2y4=−3x2y4A+C=−12x2y4+9x2y4=−3x2y4
B+C=−6x2y4+9x2y4=3x2y
a: A = -2xy + 3/2xy^2 + 1/2xy^2 + xy = -2xy + 2xy^2 + xy = 2xy^2 - xy
b: B = xy^2z + 2xy^2z - xyz - 3xy^2z + xy^2z = 3xy^2z - xyz
c: C = 4x^2y^3 + x^4 - 2x^2 + 6x^4 - x^2y^3 = 7x^4 + 3x^2y^3 - 2x^2
d: D = 3/4xy^2 - 2xy - 1/2xy^2 + 3xy = 5/4xy^2 + xy
e: E = 2x^2 - 3y^3 - z^4 - 4x^2 + 2y^3 + 3z^4 = -2x^2 - y^3 + 2z^4
f: F = 3xy^2z + xy^2z - xyz + 2xy^2z - 3xyz = 6xy^2z - 2xyz
a: A=-2xy+3/2xy^2+1/2xy^2+xy
=-2xy+xy+3/2xy^2+1/2xy^2
=2xy^2-xy
b: \(B=xy^2z+2xy^2z-xyz-3xy^2z+xy^2z\)
\(=xy^2z\left(1+2-3+1\right)-xyz=xy^2z-xyz\)
c: \(=4x^2y^3-x^2y^3+x^4+6x^4-2x^2\)
\(=7x^4-x^2+3x^2y^3\)
d: \(=\dfrac{3}{4}xy^2-\dfrac{1}{2}xy^2+3xy-2xy\)
=1/4xy^2+xy
e: \(=2x^2-4x^2-3y^3+2y^3+3z^4-z^4\)
\(=-2x^2-y^3+2z^4\)
f: \(=xy^2z+3xy^2z+2xy^2z-xyz-3xyz\)
\(=6xy^2z-4xyz\)
\(2x^2y-x^3-xy+1+x^3+2xy^2-2\)
\(=\left(-x^3+x^3\right)+\left(1-2\right)+2x^2y-xy+2xy^2\)
\(=0-1+2x^2y-xy+2xy^2\)
\(=2x^2y-xy+2xy^2-1\)
x2y4 - 2xy2 + 1
= (xy2)2 - 2xy2 + 1
= (xy2 + 1)2
Trả lời:
x2y4 - 2xy2 + 1
= ( xy2 )2 - 2.xy2.1 + 12
= ( xy2 - 1 )2